Usuários e produção da existência: contribuições de Álvaro Vieira Pinto e Paulo Freire à interação humano-computador - Gonzatto, Rodrigo Freese (2018)
In this thesis we aim to trace, characterize and strain understandings about "users" in HumanComputer Interaction (HCI) studies. "User" is a term that refers to the person who uses a computational artifact, and a concept that implies a characterization of humans and their relations with technologies. We propose the existence production as a potential approach of theoretical debate about "users" in HCI, based on studies in Science, Technology and Society (STS) by Álvaro Vieira Pinto and Paulo Freire. The existential dialectic approach of these authors requires us to consider "users" as people in construction, who produce themselves by using and developing knowledge, techniques and artifacts, through social praxis in their realities. However, the existence development, when placed in oppressive conditions, requires that subjects become aware of and overcome the oppressions that alienate their existences production. We problematize some practices and representations of "user" that constrain, hide or delegitimize the “users” autonomy in their existences social production. We point out how "users" were de-specialized of their relation with computational technologies, and their participation in these technologies production regulated and distanced from the spaces and design times legitimized by the capitalist mode of production. We discuss how "users" are reduced to a generic figure, represented as disempowered individuals or as passive interfaces recipients. However, from Vieira Pinto and Freire, we understand that these characterizations do not constitute an essence of the "user", but a historically constructed condition – which HCI is part, reinforcing and questioning. Finally, we list proposals for research and project in Human-Computer Interaction, by a existential-dialectical matrix, to evidence the existence production through the use and computational artifacts production: 1) an initial research agenda that positions "users" as subjects of knowledge and you do in HCI; 2) the category "for itself" as a design direction that aims at the social existence production, by the development of computational artifacts via emancipatory empowerment; and 3) the concept of “handiness interface" as a way of evidencing the material and subjective interactions production, carried out socially by "users", from their handiness conditions. We conclude by recommending that "users" be recognized by the Human-Computer Interaction as participants and protagonists in the social process of human-computer interactions production, and that, because of the importance that computational artifacts have in the their existences production, contributes to offer them the conditions for, with autonomy, overcome oppressions and develop for freedom.